Photostriction of CH3NH3PbBr3 Perovskite Crystals. Issue 35 (17th July 2017) - Wei, Tzu‐Chiao; Wang, Hsin‐Ping; Li, Ting‐You; Lin, Chun‐Ho; Hsieh, Ying‐Hui; Chu, Ying‐Hao; He, Jr‐Hau
Abstract : Organic–inorganic hybrid perovskite materials exhibit a variety of physical properties. Pronounced coupling between phonon, organic cations, and the inorganic framework suggest that these materials exhibit strong light–matter interactions. The photoinduced strain of CH3 NH3 PbBr3 is investigated using high‐resolution and contactless in situ Raman spectroscopy. Under illumination, the material exhibits large blue shifts in its Raman spectra that indicate significant structural deformations (i.e., photostriction). From these shifts, the photostrictive coefficient of CH3 NH3 PbBr3 is calculated as 2.08 × 10 −8 m 2 W −1 at room temperature under visible light illumination. The significant photostriction of CH3 NH3 PbBr3 is attributed to a combination of the photovoltaic effect and translational symmetry loss of the molecular configuration via strong translation–rotation coupling. Unlike CH3 NH3 PbI3, it is noted that the photostriction of CH3 NH3 PbBr3 is extremely stable, demonstrating no signs of optical decay for at least 30 d. These results suggest the potential of CH3 NH3 PbBr3 for applications in next‐generation optical micro‐electromechanical devices. Abstract : The photoinduced strain of CH3 NH3 PbBr3 is investigated using high‐resolution and contactless in situ Raman spectroscopy. Under illumination, the material exhibits large blue shifts in its Raman spectra that indicate significant structural deformations. The significant photostriction of CH3 NH3 PbBr3 can be attributed to a combination of the photovoltaic effect and translational symmetry loss of the molecular configuration via strong translation–rotation coupling.